Friction on air wheels: a special towed air wheel - Шифрин, Б.М. (Problems of Tribology, 2015)
With the help of well-known mathematical models of low-dimensional dynamics the paper solves direct problem of dynamics of a rolling air wheel. The paper restricts itself to small slip angles and zero camber angle, neglects slip zone at the contact patch of the tire with the plane and finds the lateral force of friction and restoring moment. The author uses the model of M.V. Keldysh and its simplified version for hard tire and the model of steady withdrawal. It is shown that at a certain length of air wheel tow (i.e. for special towed air wheels) temporal laws of change for thrust rotation angles, lateral friction and restoring moment coincide up to constant size multiplier factors. In this case, regardless of the hardness of the tires, the original and the above-mentioned simplified models by M.V. Keldysh lead to the same results. The case of a special towed air wheel is convenient to use in the process of building a more complete model of friction — for testing its work in cases of small-angle slip.